Active Methodologies in the Legal Research Preparedness of the Human Sovereignty’s Connatural Law (Docentes 2.0 Journal, 2024)
Human Rights as an international and internal norm also connote legality and legal order in the present reality, in the world, as well as in the space of the State. However, the natural, cultural, and legal categories are still delimited, and sovereignty is not being established. Human.   Conceptualizing the knowledge and the scientific-legal method, it was possible to distinguish foundations and stages of the qualitative approach investigative process using basic principles with the application of active methodologies for the teaching of Unnatural Law as part of Legal Research with an epistemic process that makes logic, and They express the nature of laws within legal-scientific research. Managing to transform learning into an authentic and effective result of education, the essence was investigated with legal, scientific analysis in search of proving or refuting the hypothesis to propose a scientific truth or certain reality. By analyzing legal categories of International Law and internal or State rights with active methodologies, it was possible to know that they are in the evolutionary development of society constituting legal security - legal security of the right of sovereignty for the States, but not yet for the people, to whom it does not grant ownership and full exercise of their connatural rights in International Law. Currently, it is necessary to coherently establish the universalization of the free exercise of connatural sovereignty by international law, as well as state law, even considering that connatural sovereignty emanates from inalienable rights with which man was born who delegates its exercise and power that emanates from it, preserving it to coexist with its evaluative and axiological content.
Keywords: Participatory methodologies; transformative learning; human rights; human sovereignty; international law